Análisis jurídico y doctrinario de la duración del proceso de adopción de niñas, niños y adolescentes en la legislación ecuatoriana - Méndez Cahueñas, Jhulissa Gabriela (2022)
The present research work has been developed within the legal field, the problem on which this research focuses is about the duration of the adoption processes of children and adolescents as they do not have a time limit to develop. It is known that adoption is one of the means by which the State provides an ideal family for children and adolescents who lack a family, despite that there are some failures within this institution. It is true that within the Organic Code of Children and Adolescents the process to be followed and the requirements that must be met to adopt are established, but the problem arises at the moment that the processes begin to have too much bureaucratic obstacle and the procedures take months or years to develop, this because, there is no time limit within legislation. This research seeks to determine how important the adoption process is, especially that its administrative phase is developed within a certain time in an agile and safe way for minors, since, in that article 165 of the Organic Code of Children and Adolescents establishes the studies, reports and analyses that will be developed to be able to adopt, but it does not stipulate in what time it will be developed. At present, each procedure that must be carried out in this process is chaotic and extensive, which leads to the children who are waiting to be adopted to continue without a family, this also leads to the future adoptive parents desisting from the process and the most affected are the minors, since they are the ones who need a family that ensures their well-being. In our country there are many processes of adoption of children or adolescents that have not yet been completed despite the fact that they have been presented years ago, that is why it is considered that if the time is regulated for the Ministry of Economic and Social Inclusion, specifically the Technical Units of Adoption and Family Assignment Committees to present the required reports and studies the processes will advance in a fast way which will advance in a fast way which helps meet the goal of adoption. Based on the above, it is considered necessary to develop an investigation where a legal reform was proposed to Article 165 of the Organic Code of Children and Adolescents in which a duration time is established for the administrative phase of adoption and thus help to eradicate the bureaucracy that exists within this process.